Moving pictures - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The Television Trust for the Environment (TVE) specializes in the making and distribution of films concerned with environmentalissues. Moving pictures 6 is the title of their sixth distribution catalogue containing details of 362 programmes. The...